2020
DOI: 10.3390/ijms21030840
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Neutrophil Activation Markers Predict Venous Thrombosis in Pancreatic Ductal Adenocarcinoma and Distal Extrahepatic Cholangiocarcinoma

Abstract: Cancer-associated venous thrombosis (VTE) increases mortality and morbidity. However, limited tools are available to identify high risk patients. Upon activation, neutrophils release their content through different mechanisms, thereby prompting thrombosis. We explored plasma microRNAs (miRNAs) and neutrophil activation markers to predict VTE in pancreatic ductal adenocarcinoma (PDAC) and distal extrahepatic cholangiocarcinoma (DECC). Twenty-six PDAC and 6 DECC patients recruited at cancer diagnosis, were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 61 publications
0
37
1
1
Order By: Relevance
“…The causes of thrombosis are both genetic and acquired; however, despite the large increase in the number of identified risk factors, still a substantial number of thrombotic events occur spontaneously without an apparent origin, which may reflect causes not yet discovered. Provided the interplay between immunity and thrombosis, where neutrophils play a predominant role; markers of neutrophil activation may allow identifying patients with high thrombotic risk, as we previously demonstrated in cancer patients [33,34]. Thus, we explored the relation of neutrophil activation markers and the risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The causes of thrombosis are both genetic and acquired; however, despite the large increase in the number of identified risk factors, still a substantial number of thrombotic events occur spontaneously without an apparent origin, which may reflect causes not yet discovered. Provided the interplay between immunity and thrombosis, where neutrophils play a predominant role; markers of neutrophil activation may allow identifying patients with high thrombotic risk, as we previously demonstrated in cancer patients [33,34]. Thus, we explored the relation of neutrophil activation markers and the risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Following the strategy addressed in previous studies [25][26][27][28][29]33,34,54,55], we evaluated whether the different markers of neutrophil activation measured in plasma had the same cellular origin by means of their correlation. We found a significant correlation between levels of cfDNA and calprotectin (r = 0.28; p < 0.0001), similar to that observed in previous plasma studies [27,33], and also between neutrophil count and calprotectin (Spearman r = 0.18; p = 0.003) indicating that they might have, to some extent, the same origin, probably an increased activation of neutrophils or NETosis. Additionally, the inflammatory marker NLR has been previously ascertained as a simple and valuable marker for VTE prognosis [56][57][58][59] and also for other thrombotic disorders [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies suggest that microparticles carry both nuclear and cytoplasmic ribonucleic acid (RNA) [83] and deoxyribonucleic acid (DNA) [84], especially microRNA. Additionally, microparticles have an important role in transferring microRNA from endothelial progenitor cells to endothelial cells, and this horizontal transfer of genetic mass between platelets and endothelial cells may influence thrombosis [14].…”
Section: Microparticlesmentioning
confidence: 99%
“…Even though several risk stratification tools have been proposed to identify a subset of cancer patients at high risk of developing VTE, their clinical usefulness remains under debate [56]. It is of interest that in a recent study, Oto et al (2020) [57] identified a profile consisting of 7 miRNAs (miR-486-5p, miR-106b-5p, let-7i-5p, let-7g-5p, miR-144-3p, miR-19a-3p, and miR-103a-3p) associated with the occurrence of a future VTE event during follow-up in a cohort of 32 patients with pancreatic ductal adenocarcinoma and distal extrahepatic cholangiocarcinoma.…”
Section: Epidemiological Studies: Mirnas and Venous Thromboembolismmentioning
confidence: 99%